A new species of Leptolalax (Anura: Megophryidae) from Son Tra Peninsula, central Vietnam - Nguyen, Luan Thanh; Poyarkov, Nikolay A. Jr.; Le, Dzung Trung; Vo, Ba Dinh; Phan, Hoa Thi; Duong, Tang Van; Murphy, Robert W.; Nguyen, Sang Ngoc (Zootaxa, 2018)
Morphological, acoustic and molecular analyses result in the description of Leptolalax rowleyae sp. nov., a new species of frog in the Megophryidae, belonging to the L. applebyi Rowley & Cao species group from central Vietnam. It differs from its congeners by a combination of the following morphological attributes: (1) adult SVL 23.4–25.4 mm in males and 27–27.8 mm in females; (2) presence of distinct dark/brown dorsolateral markings, including black spots on flanks; (3) pinkish milk-white to light brown chest and belly with numerous white speckles; (4) tympanum distinct; (5) absence of webbing or lateral dermal fringes on fingers and toes; (6) pectoral glands comparatively small (3.3–4.7% of SVL); (7) ventrolateral glands indistinct; and (8) iris bicolored with copper tint in upper half fading to golden in lower third of iris. The male advertisement call of the new species consists of 4–6 notes, lacking a distinct introductory note, with an average dominant frequency of 3.2–3.5 kHz. The description of the tadpole constitutes the first description of larval morphology for a member of the L. appleybi species group. Genetically, an uncorrected sequence divergence of 7.4% for 16S rRNA separates the new species from its two closest relatives, L. ardens and L. melicus in the L. applebyi species group.